국가기록포털 검색서비스 품질 점검을 위한 평가셋 구축 및 현황 분석 - 나정호(Jeong Ho Na), 소현기(Hyeon-Gi So), 염경록(Gyung Rok Yeom), 이정옥(Jung-Ok Lee), 오효정(Hyo-Jung Oh) (Journal of Records Management & Archives Society of Korea, 2022)
The ultimate record management's purpose is preservation and utilization. However, the National Archives of Korea (NAK)s Portal has problems such as search system aging and search tools dualization. As a result, the users' search satisfaction is not satisfied, and the improvement demand increases. This study aimed to evaluate the NAK's search quality as a preliminary study for NAK search system advancement. To this end, we analyzed the current status of CAMS and NAK's Portal. Then, we established the test sets and evaluated the NAK's Portal quality from the user's point of view. Evaluation results were analyzed using Precision, Recall, F-score, and MRR. The analysis results showed that the overall search performance was low, particularly in the "advanced subject search," which showed low performance in Precision, Recall, and MRR. Thus, improvement is urgently needed. The test sets established for this study are expected to be used as a basis for objectively measuring the improvement of the search performance after the NAK search system advancement. 기록을 관리하는 궁극적인 목적은 안전한 보존과 효율적 활용이다. 그러나 공공기록물 관리의 수장인 국가기록원의 검색서비스인 국가기록포털은 검색 시스템이 도입된 지 10년이 넘어 노후화되었고, 검색도구도 이원화되어 있다. 또한, 국가기록물을 열람하고자 하는 이용자의 검색 만족도를 충족시키지 못해 개선이 필요하다. 본 연구는 국가기록물 검색 고도화를 위한 사전 연구로, 현재의 국가기록원 검색시스템의 검색 품질 현황을 파악하는 것을 목적으로 한다. 이를 위해 국가기록원에서 사용 중인 검색도구인 CAMS와 국가기록포털의 현황을 분석하고 검색서비스 품질을 점검하기 위한 평가셋을 구축, 이용자 관점에서 국가기록포털의 검색 품질 평가를 실시하였다. 국가기록포털의 성능평가를 위한 척도로는 정확률과 재현율, F-score, MRR 등을 활용, 다양한 각도에서 분석하였다. 검색 품질 평가결과 전반적으로 검색 성능이 낮은 것으로 나타났으며, 특히 '주제별상세검색'의 경우 정확률, 재현율, MRR이 모두 낮게 나와 개선이 시급할 것으로 보인다. 본 연구를 통해 구축된 평가셋이 향후 국가기록원 검색시스템의 고도화 이후 시스템의 성능이 얼마나 개선되었는지를 객관적으로 측정할 수 있는 기틀로 활용되기를 기대한다.